Development of a Computer-Based Interactive Video Formative Feedback to Improve Students' Conceptual Understanding of Static Fluid - Irawan, Ivan Danar Aditya; Kusairi, Sentot; Khusaini, Khusaini; Basri, Nur Akhyar; Dahlan, Ahmad (Universitas Muhammadiyah Makassar, 2025)
Physics education, particularly in static fluid concepts, often suffers from students' low conceptual understanding due to the limited availability of tailored formative feedback. To address this issue, this study aimed to develop and validate a computer-based interactive-video formative feedback model that supports independent learning and improves students' comprehension of static fluids. Employing the 4D Research and Development model (Define, Design, Develop, and Disseminate), the study focused on the first three stages and involved 128 high school students. The validity of the media was assessed by content and media experts, yielding high validity scores (97% for content and 93% for media). A practicality test showed an 83% approval rate, indicating strong usability and relevance for classroom and independent use. Effectiveness was further assessed through pretest and posttest analysis using the Wilcoxon and N-Gain tests. Results demonstrated a statistically significant improvement in students' conceptual understanding (p < 0.001), although the N-Gain value of 0.27 classified the effectiveness as low. Despite this limitation, students responded positively to the interactive format, citing increased engagement and clarity. The novelty of this study lies in integrating isomorphic questions with animated feedback and audio explanations in an interactive video format tailored to students' interests. This research contributes to physics education by offering a practical, validated digital tool that enhances formative assessment practices and provides a foundation for future improvements in instructional media for abstract topics like static fluid.